URETROSTOMIA EM CÃO: RELATO DE CASO - da Silva, Leciane Rodrigues; Rutcoski, Vitória Modelski; Bavaresco, Kelly Cristina; Vaccarin, Charline Vanessa; Festugatto, Rafael; Lusa, Tatiane; Wurfel, Simone de Fátima Rauber (Anais de Medicina Veterinária, 2022)
.